Analisis Pemasaran Sapi di Kabupaten Batubara - Imam, Fahrizal; Hasnudi, Hasnudi; Sembiring, Rasmulia; Siregar, Tumpal H.S. (Universitas Medan Area, 2019)
This study aims to identify and analyze marketing channels, marketing margins, farmer share levels, marketing efficiency and cattle marketing strategies in Batubara Regency. This research was conducted in May - June 2017. The research location was selected by purposive sampling and carried out in 3 (three) districts, Lima Puluh, Sei Suka, and Medang Deras Districts. The research respondents were taken by classified random sampling as many as 85 cattle farmers, and the sample of traders selected by snowball ball sampling were 11 local collectors and 2 large traders. Data analysis was performed descriptively quantitative. The results showed that there were 4 channels formed from marketing institutions namely marketing channel I (breeder-local collecting agent-big-slaughterer), marketing channel II (breeder - local-consumer collecting agent), marketing channel III (breeder-collecting agent local-traders outside the region) and marketing channels IV (breeder-consumer / butcher). The highest marketing margin is in channel I and the lowest is in marketing channel IV. The highest portion received by farmers occurred in marketing channel IV by 100% and the lowest occurred in marketing channel I. Marketing channel IV was the most efficient channel seen from the calculation of the efficiency index.